(untitled) (Medicine Today, 2017)
Male circumcision has proved to be protective for male to male HIV transmission. The effect of male circumcision on female partner’s HIV status is still uncertain from previous studies. This systematic review aimed to assess whether circumcision status of an HIV-infected male changes the risk of HIV transmission to his female sexual partner. We analyzed findings from one randomized controlled trial and 4 cross sectional study and found no significant evidence in support of our hypothesis that male circumcision prevents HIV transmission in female. Due to high methodological and clinical heterogeneity, meta-analysis was not done. Qualitative synthesis revealed lack of existing good quality study to address this question. Four of five studies reported no association between male circumcision and HIV transmission. One cohort study reported protective effect of male circumcision on their female partner’s HIV. Only one subpopulation of RCT (resume to sexual activity before wound healing) reported increased HIV transmission in female whose male partner is circumcised. Effect of male circumcision on HIV transmission is still blurred. Large scale randomized trial is needed to answer this question. Until then, the prevention programs should also emphasize other measures of HIV transmission. Medicine Today 2016 Vol.28(1): 22-26